Documentation: Definitions of Productivity (Relations industrielles / Industrial Relations, 1950)
It is fashionable these days to talk about "productivity", all the more so since the word may be used in several meanings. Only some of them are accepted by economists. To the Groupe des Statisticiens du Commissariat Général au Plan we owe a series of definitions which, in spite of the provisory character assigned to them by their authors, will assure a certain precision and stability to the senses in which this term is accepted.